Case report: Mild leukoencephalopathy caused by a new mutation of NOTCH3 gene. Issue 12 (24th March 2023) - Qi, Yuxiang; Li, Hairong; Yu, Ling
Abstract : Background: Cerebral autosomal dominant arteriosis with subcortical infarction and leukoencephalopathy (CADASIL) is a single-gene small-vessel disease of the brain characterized by migraine, recurrent ischemic stroke, psychiatric disorders, progressive cognitive decline, and occasional intracerebral hemorrhage. [1 ] NOTCH3 was identified as a pathogenic gene for CADASIL. [2 ] The NOTCH3 gene encodes a membrane-bound receptor protein, and to date, several different NOTCH3 gene mutations have been identified. [3 ] Here, we report a case of CADASIL with a heterozygous mutation c.931T > G (thymine > guanine) on the exon region of the NOTCH3 gene, resulting in an amino acid change p.C311G (cysteine > glycine). Case report: We report a case of a female patient with CADASIL whose genetic sequencing revealed a mutation in the NOTCH3 gene. However, this patient did not exhibit any of the typical clinical findings of CADASIL but the patient's cerebral magnetic resonance imaging was consistent with the characteristic findings of CADASIL. Conclusions: This case reminds us that mutations caused by different mutation sites present different clinical symptoms.